Effect of Postnatal Maternal Protein Intake on Prenatal Programming of Hypertension. (December 2014) - Siddique, Khurrum; Guzman, German Lozano; Gattineni, Jyothsna; Baum, Michel
This study examined whether postnatal maternal dietary protein deprivation during the time of nursing can program hypertension when the offspring are studied as adults. Rats were fed either a 6% or 20% protein diet during the second half of pregnancy and continued on the same diet while rats were nursing their pups. The neonates of all of the rats were cross-fostered to a different mother and studied as adults. Adult rats that had a normal prenatal environment but were reared by mothers fed a low-protein diet until weaning (20%-6%) were hypertensive, had a higher renal Na + -K + -2Cl − cotransporter (NKCC2) and Na + -Cl − cotransporter (NCC) protein abundance yet a comparable number of glomeruli, and had higher plasma renin and angiotensin II levels compared to control (20%-20%). Rats whose mothers were fed a 6% protein diet and cross-fostered to a different rat fed a 6% protein diet until weaning (6%-6%) were hypertensive, had elevated plasma renin and angiotensin II levels, and had a reduction in nephron number but had NKCC2 and NCC levels comparable to 20% to 20% offspring. The 6% to 20% had blood pressure and glomerular numbers comparable to 20% to 20% rats. The hypertension resulting from prenatal dietary protein deprivation can be normalized by improving the postnatal environment. Combined prenatal and postnatal maternal dietary protein deprivation and maternal dietary protein deprivation while nursing alone (20%-6%) results in hypertension, but the mechanism for the hypertension in these groups is different.